2019
DOI: 10.1101/594861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

StanDep: capturing transcriptomic variability improves context-specific metabolic models

Abstract: AbstractDiverse algorithms can integrate transcriptomics with genome-scale metabolic models (GEMs) to build context-specific metabolic models. These algorithms require identification of a list of high confidence (core) reactions from transcriptomics, but parameters related to identification of core reactions, such as thresholding of expression profiles, can significantly change model content. Importantly, current thresholding approaches are burdened with setting singular arbitr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Several studies have indicated that not all genes or enzymes are active in a given cell line or culture condition [6,12]. In this regard, it is required to create context-specific (i.e., cell line-specific or condition-specific) models.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that not all genes or enzymes are active in a given cell line or culture condition [6,12]. In this regard, it is required to create context-specific (i.e., cell line-specific or condition-specific) models.…”
Section: Introductionmentioning
confidence: 99%